Effects of AHCC® on Immune and Stress Responses in Healthy Individuals - Jun Takanari; Atsuya Sato PhD; Hideaki Waki PhD; Shogo Miyazaki PhD; Kazuo Uebaba MD, PhD; Tatsuya Hisajima PhD (SAGE Publishing, 2018)
AHCC® is a functional food from the basidiomycete Lentinula edodes . We evaluated the effects of AHCC® on subjects under different kinds of stress and at rest. Physical stress was imposed using an active standing test, known as Schellong's test. Sympathetic nervous activity in the standing position was significantly greater in AHCC®-treated subjects than in a placebo group. In contrast, AHCC® significantly increased parasympathetic nervous activity at rest. Under mental stress, AHCC® increased sympathetic nervous activity, with no difference in the parasympathetic nervous system. In subjects with chronic mental stress, self-reported "initiation and maintenance of sleep" was significantly greater in the AHCC®-intake period than in the placebo intake period, and natural killer cell activity also increased after AHCC® intake, suggesting a possible mechanism of action of AHCC®. Our findings indicate that AHCC® is potentially effective in stress management and may be useful in the treatment of depression.